2020
DOI: 10.1038/s41598-020-62594-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-124 Reduces Arsenic-induced Endoplasmic Reticulum Stress and Neurotoxicity and is Linked with Neurodevelopment in Children

Abstract: Arsenic (As) exposure adversely affects neurodevelopment in children. Accumulation of misfolded proteins in cells exposed to As leads to endoplasmic reticulum (ER) stress response, which, if not relieved, results in cell death. Despite the potential role of ER stress for As-induced neurotoxicity, the underlying mechanisms remain poorly understood. Here we aimed to investigate the roles of microRNA(miR)-124, a novel ER stress suppressor, in As-induced ER stress response and cytotoxicity in neural cells. We furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…In this regard, miR-124 has been identified as a suppressor of ER stress-induced apoptosis (Panganiban et al, 2019 ), and a recent study demonstrated the neuroprotective role of miR-124 during arsenic-induced ER stress. Interestingly, genetic polymorphisms of miR-124 are associated with neurocognitive outcomes in children (Park et al, 2020 ). This study identifies miR-124 as a potential therapeutic target against arsenic-induced ER stress and neurotoxicity.…”
Section: Human Disorders Due To Arsenic Exposurementioning
confidence: 99%
“…In this regard, miR-124 has been identified as a suppressor of ER stress-induced apoptosis (Panganiban et al, 2019 ), and a recent study demonstrated the neuroprotective role of miR-124 during arsenic-induced ER stress. Interestingly, genetic polymorphisms of miR-124 are associated with neurocognitive outcomes in children (Park et al, 2020 ). This study identifies miR-124 as a potential therapeutic target against arsenic-induced ER stress and neurotoxicity.…”
Section: Human Disorders Due To Arsenic Exposurementioning
confidence: 99%
“…As-induced apoptosis interrupted neurodevelopment in rats, leading to cognitive impairment . As exposure resulted in abnormal histological changes in mouse cerebral cortex tissue, neuronal degeneration, cytological changes, and cell shrinkage .…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are coded by genes, so for their screening, the same rules as for protein-coding genes can be applied. For example, Panganiban et al (2019) uncovered multiple suppressors of endoplasmic reticulum stress via CRISPRn screening, among which was miRNA-124, and indeed in a further study miRNA-124 has shown to provide protection from arsenic-induced endoplasmic reticulum stress and a potential therapeutic target to counteract arsenic exposure ( Park et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%